BanKs versus Credit Cooperatives: An analysis of the effiCienCy ratios and revenues from serviCe provision between 2002 and 2012 - Matias, Alberto Borges; de Miranda Quaglio, Gislaine [UNESP]; de Lima, João Paulo Resende; Magnani, Vinícius Medeiros (My University, 2014)
The objective in this descriptive study is to analyze the efficiency ratio and evolution in the revenues from credit cooperatives’ service provision in comparison with private and public banking institutions. According to data from the Brazilian Central Bank, in 2012, the GDP/credit index corresponded to 55.5%, which cannot be compared yet with that of developed countries, where the ratio surpasses 100%. The sample includes the largest banks and cooperatives, selected based on their “total assets”, totaling an average 69.31% for the banks and 61.33% for the credit cooperatives. To analyze the variables, efficiency ratios and vertical and horizontal analysis of the revenues from service provision were used for the period between 2002 and 2012. The efficiency ratio is an important indicator, as it relates the inputs applied in the production with the products obtained in that process. The analysis of the revenues from service delivery is significant, demonstrating increasing relevance in financial institutions’ financial performance. The obtained results demonstrated that the private banks’ efficiency ratios are the highest among the segments analyzed, followed by the public banks and, finally, by the credit cooperatives. The predominance of the private banks was not affected by the crisis years, as opposed to the public banks, which were bypassed by the cooperative segment in the years 2008-2009 and 2012. In view of the accounts that constitute the ratio, it was verified that until 2006 the commitment of the Gross Income from Financial Intermediation to the structural expenses in the cooperatives was similar to the public banks, but higher than in the private banks. This behavior only differed in 2007-2010 and 2012, which this indicator only dropped in the cooperative segment. In the horizontal and vertical evolutions, it was verified that, despite the significant growth registered by the credit cooperatives and the convergence in the degree of participation among the segments, the share of the revenues from service provision remains higher in the banking than in the credit cooperative segment. This fact may represent a potential element for the cooperatives to explore in the search for efficiency.
bancos versus cooperativas de crédito: um estudo dos índices de eficiência e receita da prestação de serviços entre 2002 e 2012
Keywords: Efficiency. Banks. Credit cooperatives. Revenues from service provision. Credit market